Effect of Growth Rate on Resistance of Candida albicans Biofilms to Antifungal Agents - Baillie, George S. (American Society for Microbiology, 1998)
A perfused biofilm fermentor, which allows growth-rate control of adherent microbial populations, was used to assess whether the susceptibility of Candida albicans biofilms to antifungal agents is dependent on growth rate. Biofilms were generated under conditions of glucose limitation and were perfused with drugs at a high concentration (20 times the MIC). Amphotericin B produced a greater reduction in the number of daughter cells in biofilm eluates than ketoconazole, fluconazole, or flucytosine. Similar decreases in daughter cell counts were observed when biofilms growing at three different rates were perfused with amphotericin B. In a separate series of experiments, intact biofilms, resuspended biofilm cells, and newly formed daughter cells were removed from the fermentor and were exposed to a lower concentration of amphotericin B for 1 h. The susceptibility profiles over a range of growth rates were then compared with those obtained for planktonic cells grown at the same rates under glucose limitation in a chemostat. Intact biofilms were resistant to amphotericin B at all growth rates tested, whereas planktonic cells were resistant only at low growth rates (≤0.13 h(−1)). Cells resuspended from biofilms were less resistant than intact biofilm populations but more resistant than daughter cells; the susceptibilities of both these cell types were largely independent of growth rate. Our findings indicate that the amphotericin B resistance of C. albicans biofilms is not simply due to a low growth rate but depends on some other feature of the biofilm mode of growth.